News Media Coverage and Public Reactions to a Red Tide at the Algarve Coast (Southern Portugal) - Domingues, Rita B. (Journal of Tourism, Sustainability and Well-being, 2021)
In June 2019, a red tide caused by the dinoflagellate Lingulodinium polyedra, whose toxins do not cause harm in humans, developed in the Algarve coast (southern Portugal). The occurrence of algal toxins and consequent interdiction of bivalve harvesting is common in this region, but harmful algal blooms that lead to water discolouration are rare. This study analyses the scientific accuracy of the information communicated by news media, and consequent public reactions, by analysing news pieces shared on Facebook by regional and national news media outlets, and comments to the news posted by individual users. Overall, news pieces had a sensationalized, negative tone, and many lacked scientific accuracy. For instance, some news referred that ingestion of contaminated water, fish, and shellfish leads to gastrointestinal problems, and the toxic substances that the algae produce may contaminate the air and cause respiratory difficulties – which is false in the case of a L. polyedra bloom. Many commenters showed an adverse reaction to the event, most likely influenced by the negative portrayal of the red tide by news media. Other Facebook users were quite knowledgeable about the red tide, due to their previous experience with these events. Individuals seemed to be aware of the lack of cooperation between authorities and scientists and expressed their mistrust in these stakeholders. As red tides may become a common feature in the Algarve coast, journalists, scientists, and authorities should strive to offer accurate and responsible information to the public.